Pengaruh Karakteristik Pekerjaan Karakteristik Organisasi Dan Karakteristik Individu Terhadap Kepuasan Kerja Pegawai (Studi Pada SMK Terpadu AL-Ishlahiyah Singosari Kabupaten Malang) - Anggriani, Rini; Djaelani, Abdul Kodir; Rahmawati, Rahmawati (UNIVERSITAS ISLAM MALANG, 2024)
Abstract Job satisfaction is the level of pleasure a person feels regarding their role or work in an organization. The degree to which an individual feels satisfied that they are getting a defined balance of various aspects of the job situation of the organization in which they work. The aim of this research is to determine the partial and simultaneous influence of job characteristics, organizational characteristics and individual characteristics on employee job satisfaction at AL-Islahiyah Singosari Integrated Vocational School, Malang Regency. The quantitative research method uses multiple linear regression with a sample size of 41 people. Based on the research results, job characteristics have a positive and significant effect on employee job satisfaction, organizational characteristics have a positive and significant effect on employee job satisfaction, individual characteristics have a positive and significant effect on employee job satisfaction. And simultaneously job characteristics, organizational characteristics, and individual characteristics together have a positive and significant effect on job satisfaction of employees of AL-Islahiyah Singosari Integrated Vocational School, Malang Regency. There is a need to look for other variables that can be factors that influence employee job satisfaction. Keywords: Job Characteristics; Organizational Characteristics; Individual Characteristics; Employee Job Satisfaction